2022
DOI: 10.1177/2050313x221110994
|View full text |Cite
|
Sign up to set email alerts
|

Abscess of ligamentum teres hepatis post-endoscopic retrograde cholangiopancreatography: A case report and a literature review

Abstract: Abscess of the ligamentum teres hepatis has been described in the medical literature as an extremely rare clinical entity, which often presents a diagnostic dilemma. A 68-year-old man was hospitalized for upper abdominal pain and obstructive jaundice. The patient presented with low-grade intermittent fever. Laboratory investigations showed a white blood cell count of 32.38 × 109/L, a C-reactive protein level of 247.86 mg/L, abnormal liver enzyme and bilirubin levels, and elevated serum levels of amylase and li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…Informed consent for ERCP should address at least these six possible complications: (a) acute pancreatitis, (b) bleeding, (c) infections, (d) cardiorespiratory events, (e) hypersensitivity reaction, and (f) perforation [ 1 ]. Clinically significant bacteremia post-ERCP occurs in up to 5% of patients [ 7 - 8 ]. Our patient had multiorganism bacteremia: Klebsiella pneumoniae and Enterococcus faecalis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Informed consent for ERCP should address at least these six possible complications: (a) acute pancreatitis, (b) bleeding, (c) infections, (d) cardiorespiratory events, (e) hypersensitivity reaction, and (f) perforation [ 1 ]. Clinically significant bacteremia post-ERCP occurs in up to 5% of patients [ 7 - 8 ]. Our patient had multiorganism bacteremia: Klebsiella pneumoniae and Enterococcus faecalis.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the patient's worsening critical condition, the patient was managed only per comfort-care measures and did not undergo any interventions. Similarly, Ji et al reported an interesting case when a patient developed a ligamentum teres hepatic abscess after an ERCP and underwent laparoscopic drainage of the abscess with complete recovery [ 7 ]. Sonography and/or CT scans are primarily used to diagnose hepatic abscesses, with needle aspiration for bacteriology studies to confirm the diagnosis if needed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the high recurrence rate of choledocholithiasis has become the focus of attention for surgeons worldwide[ 6 ]. Presently, domestic and foreign studies on the recurrence mechanism of choledocholithiasis mainly focus on crucial issues such as biliary microecology, duodenal papilla sphincter functional damage and abnormalities caused by surgery, and individual biliary anatomical differences[ 7 ].…”
Section: Introductionmentioning
confidence: 99%